Strengthening Students' Faith and Piety through Learning Asmaul Husna Al-Hafiz at SD Negeri 091307 Nagahuta - Ariani, Juliatri; Ferawati; Silalahi, Johor M; Mulyani, Sri; Lubis, Salmah (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to explore the effectiveness of integrating Asmaul Husna Al-Hafiz into religious education to strengthen students' faith and piety at SD Negeri 091307 Nagahuta. In an era of rapid globalization and technological advancement, character education rooted in spiritual values has become increasingly essential. Asmaul Husna, the 99 beautiful names of Allah, embodies divine attributes that, when internalized by students, can foster a deeper understanding of Islamic values, enhance moral conduct, and build stronger spiritual awareness. Using a qualitative descriptive method, this research involved classroom observations, interviews with teachers and students, and document analysis to examine the implementation and impact of Asmaul Husna Al-Hafiz learning in daily classroom activities. The results indicate that the structured and consistent recitation, memorization, and reflection on the meanings of Asmaul Husna significantly contribute to shaping students’ religious character, promoting positive behavior, and increasing engagement in religious practices. Teachers reported improved student discipline, respectfulness, and emotional self-regulation, while students expressed a deeper connection with their faith and a greater sense of peace and purpose. This study suggests that incorporating Asmaul Husna in religious learning is a practical and impactful strategy to nurture students’ faith and piety from an early age. The findings provide valuable insights for educators, curriculum developers, and policymakers seeking to reinforce spiritual development as a core component of primary education.